Soft justice: revealing the role of criminal mediation in bringing the perpetrator and the victim together - Badrddine, Younes (Milev Journal of Research and Studies, 2022)
Some consider criminal mediation as a kind of soft justice, through which conflict that falls under the authority of the Penal Code is dealt with in a fundamentally different way from the method used in criminal proceedings. According to this point of view, criminal mediation is not seen as a simple mechanism for managing disputes, or an alternative to justice, but rather as a method of social organization aimed at restoring relations between different parts of society.